The influence of reconciliatory exercises in accordonce with sensuous preterential rate to learn tritting and communion of the ball in hadball - Sulaiman, Hamid; Bdeoi, Thabet (Journal of Physical Education, 2015)
This study focuses on the fact that people develop and build their societies depending on learning and teaching. sport lesson has a vital role in building the individual's personality and growing fittness. These exsecises increase the speed of learning handball based on the collective sports distingushed by its high skills and plaers must have different capacities. The problem in which this research is dealing with is that there is a clear decrease in learning how to deal with is that (tritting)whilt playing handball. sport teachers lessen the contraction on reconciliatory and sensuous exescises using the ball. they also don't recognize students preferences in accordonce with students' sensuous preferential learning